PERMOHONAN PENGANGKATAN ANAK DI PENGADILAN NEGERI BAJAWA PADA 04 JANUARI 2021 (STUDI KASUS PERKARA PERDATA: 1/Pdt. P/2021/PN BAJAWA) - liu, mario delourdez; Hedewata, Agustinus; Jacob, Yossie (Artemis Law Journal, 2023)
Adoption is a legal act that transfers a child from the sphere of power of parents, legal guardians or other persons responsible for the care, education and upbringing of the child into the family environment of the adoptive parents. The formulation of this problem is: (1) What is the process of adoption of children in the Bajawa District Court, (2) What are the obstacles in the process of adopting children in the Bajawa District Court, (3) How is the judge's consideration in determining the adoption of children based on civil case studies: 1/Pdt.P/ 2021/ PN Bajawa, This research uses empirical juridical method, namely research whose data is obtained directly from the research location From the results of the research found, the process of adoption of children, the applicant or candidate has taken care of the administration for registration of the child adoption application plan at the Bajawa District Court.The results of this study show: (1) The process of adoption of children in the Bajawa District Court The applicant must prepare the requirements in the law such as KTP, KK, Child birth certificate, husband and wife marriage certificate, recommendation letter, salary slip, so that it can be the basis for being able to raise a child, and there must be a letter of permission from the local government, (2) Obstacles in the process of adoption of children in the Bajawa District Court are: (a) The lack of information from the public regarding the procedural procedure or submission of an application for Adoption of Children, (b) The lack of public knowledge means that the applicant uses the services of an advocate as a legal representative, (c) Incomplete evidence and if the formal examination is not completed it becomes an obstacle in the judge's consideration. Keywords: Children, Child Adoption